Mitigating The Impacts of Secondary Trauma in K-12 Educators - Lasha Luciw (Canadian Society for Studies in Education, 2024)
Given the prevalence of adversity experienced by students attending K-12 schools, educator roles have evolved to include supporting student mental health through trauma-informed practice. What remains largely unaddressed, are the impacts of student trauma on the educators who support them, as well as best practices for alleviating this stress in school personnel, as part of a trauma-informed approach. With secondary trauma being an understudied construct in educators, this systematic literature review provides an overview of studies on how secondary trauma impacts educators, as well as approaches to supporting educator mental health following indirect trauma exposure. Qualitative data analysis resulted in the identification of themes surrounding secondary trauma impacts, including emotional and psychological affects, burnout and compassion fatigue, educator attrition, and effects on student outcomes. Themes related to mitigation strategies included individual and organizational approaches. Although best practices for mitigating secondary trauma in educators include a combination of interventions, organizational practices superseded those required by individuals alone. Thus, this review also calls for greater attention from administrators and educational policymakers to invest in further research and management of secondary trauma at an organizational level. A limitation of this research is the lack of empirical information on the impacts of secondary trauma in educators, and research-based ways to support staff affected, given the dearth of studies that currently exist.   Keywords: secondary trauma, educators, school personnel, mental health, organizational practices